Documenting the effects of the media on alcohol consumption in central Kenya - Morris, Andrew (Kansas State University, 2015)
Kenyan society has seen problems with alcohol abuse and has seen many deaths related to illicitly brewed alcohol. A Kenyan government body, The National Authority for the Campaign Against Alcohol and Drug Abuse (NACADA), has done research about the problem, but very few outsiders have performed research in this area. This research seeks to study the problem from outside of the standard government framework while using a cultural approach. The purpose of this project is to document the alcohol abuse problem in Kenya, and what methods of mass communication, if any, could be used to help convey a solution to the problem. It is to provide a firsthand account of the alcohol abuse problem that plagues the East African nation in an effort to bring more and awareness to the situation. To document the situation, I interviewed several key cultural figures chosen based on their affiliation with the academic, religious, medial or cultural framework of Kenyan society. Each person was asked a serious of questions regarding the alcohol problem in Kenya, what could be done from their particular perspective, and how the media have and could influence the situation. The information gathered indicated that the alcohol problem is widespread in Kenya, that the people with alcohol problems tend to be men, and that the problem is multifaceted and very complex. Many factors contribute to the problem, such as idleness, poverty, unemployment, and more, and the problem affects many more people than just the people drinking the alcohol. The information gathered is meant to help provide suggestions to helping solve this problem in Kenya. Recommendations from this research will provide guidance for those who are trying to create media campaigns to combat alcohol abuse in Kenya.
Keywords: Kenya; Alcohol abuse; Mass media; Health communication; Mass Communications (0708)